The genre of manokib and the problem of a perfect human being - Shavkat Ahmadovich, Khayitov (International Journal of Psychosocial Rehabilitation, 2020)
The author studies the works of Alisher Navoi "Khamsatul-mutahayyirin," "Holoti Sayyid Hasan Ardasher," and "Holoti Pahlavon Muhammad" in terms of genetics, historical, systematic, and aesthetic principles and comes to a definite conclusion that these three works are of the same genre with manokib. Analyzing the specifics of the genre of manokib in close connection with the problems of a perfect human being, he relies on sources, authoritative dictionaries, and Alisher Navoi’s own notes. The fact that a well-educated, well-behaved, spiritually mature person implies a perfect human personality and the basis of his personality is the image of a perfect person, as evidenced by the examples of genre works. In the article, Alisher Navoi’s compelling works show that respect for a person’s religion, spirituality, and humanity is respected, not by race, origin, nationality, wealth, state, location, or race. The great philosopher’s interpretations show that a pure and blessed man is shown in the genre of manokib, which, in the worst of circumstances, can protect from immorality, blasphemy, and sin, and does not shield his progeny. Only people who have their own destiny with people, nation, and country, who have a high level of thinking, and who have good character, deserve perfection; the taste of the hardship for the sake of its benefit is beautifully illustrated by the three works written in the genre.